Factors Affecting Sustainable Community Development in Narathiwat Province - Tuleh, Patchanee; Wangworawong, Chanathip; Sareemasae, Ibrahim; Maliprom, Chonthicha; Nuanoi, Saran; Manopkham, Phornthip; Tongintharach, Mathurose (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2020)
The objective of this study aimed to investigate the level of influencial factors affecting sustainable community development in Narathiwat province and factors affecting sustainable community development. The sampling group consisted of 400 people living in Narathiwat province. Stratified Random Sampling was used to calculate the sample size of each district. The reliability of questionnaires was tested by Cronbach’s Alpha Coefficient, accounting for 0.97. Data were statistically analyzed by employing percentage, average, standard deviation, and multiple linear regression. The results showed that the average level of influencial factors affecting the community development indicated a high level ( = 3.85, S.D. = 0.487). The most influential factor on community development was self-reliance, followed by administration, participation, and learning. The aforementioned factors assuring the prediction of sustainable development in Narathiwat province showed statistical significance, contributing to 74.30 percent (R2 = 0.743). Every factor should be promoted and developed constantly, and it should consider the local context in order to constitute sustainable development.